Kesiapan Guru Dalam Melaksanakan Pembelajaran Kurikulum Merdeka Kelas IV Di SDN 193 Pekanbaru - Safutri, Raja Ilia; Siti Quratul Ain (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2024)
The independent curriculum is a school learning curriculum which is carried out using the allocation of time that has been quoted in a variety of program structures and optimizing in terms of content so as to give students enough time to explore concepts and strengthen competencies. The purpose of this study is 1). Describe the teacher's readiness in implementing the learning of the Merdeka Curriculum. 2.) Describe obstacles in the implementation of Learning Merdeka Curriculum in SDN 193 Pekanbaru. This research method uses descriptive qualitative research with data collection techniques namely observation, interviews, and documentation. Data analysis used according to Miles and Huberman. The results of the study were the teacher had readiness in carrying out the learning of the Merdeka Curriculum in SDN 193 Pekanbaru in the form of 1). Understanding the characteristics and structure of the curriculum, 2). Learning Plan Readiness, 3). Learning implementation, 4). Readiness of Modules and Teaching Materials, 5). Facilities and infrastructure, and 6). Learning Assessment Readiness. The teacher has obstacles to the implementation of an independent curriculum in the form of human sources, infrastructure, time, and mindset.